PENINGKATAN DAYA SAING MADRASAH DI ERA SOCIETY 5.0 DENGAN STRATEGI MANAJEMEN BRANDING IMAGE DI MADRASAH - Muhammad Kholil; Fathor Rozi; Ahmad Fadholi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
This study aims to determine the branding image management strategy in MI Tarbiyatul Islam probolinggo district and the effectiveness of branding image management strategies in the era of society 5.0. This is qualitative research with the type of case study conducted at MI Tarbiyatul Islam in the city of Probolinggo. Sources of informants in this study were principals, curriculum, public relations, teachers, staff, and students. Then to select and determine the informants in this study, the researchers used a purposive sampling technique. Data collection techniques in this study used content/document analysis techniques, in-depth interviews, and events/observations. The method used to check the validity of the data is the triangulation method. The data analysis technique used in this research is interactive model analysis. The stages in analyzing the data in this study are data reduction, data presentation, and conclusion. The results in this study indicate that first, MI Tarbiyatul Islam applies a branding image management strategy to increase the competitiveness of madrasas in the era of society 5.0. Second, the branding image management strategy is done by; Branding management strategy planning in the period of society 5.0, Branding Image Management Strategy, Result Branding Image, and Continuous Improvement. The implications obtained by carrying out a branding image management strategy can increase public trust in choosing Madrasah Ibtidaiyah Tarbiyatul Islam institutions